Polymyositis as a Rare Musculoskeletal Manifestation of Chronic Graft-Versus-Host Disease: A Case Report of a 33-Year-Old Patient - Ben-Nun, David (International Journal of Medical Students, 2020)
Background: Musculoskeletal manifestations of chronic Graft-Versus-Host Disease (GVHD) are rare and unfamiliar to most clinicians. Here we discuss the pathophysiology of chronic GVHD, current treatments and direction of research for improved therapy and prophylaxis and focus on the common and less common musculoskeletal complications of this unfortunately prevalent and burdensome disease. The Case: This is a case report of a 33-year-old male with a past medical history of Acute Myeloid Leukemia (AML) who presented with a 1-month history of generalized, proximal weakness and was found to have polymyositis secondary to chronic GVHD. Elicitation of further history showed that the patient had had multiple manifestations of both acute and chronic graft-versus-host disease in the two years following hematopoietic stem cell transplantation (HSCT). Conclusion: It is important for clinicians to be familiar with polymyositis secondary to chronic GHVD, which may appear in patients more than 100 days following allogenic HSCT and typically presents as diffuse, generalized myopathy with preserved sensation and elevated CPK and aldolase. The current mainstay of treatment is glucocorticoids with or without a calcineurin inhibitor, however due to the side effects associated with long term treatment, more effective prophylactic and therapeutic treatments are needed to address this and other manifestations of chronic GVHD.